2012
DOI: 10.1002/etc.1811
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hormonal activities and genotoxicity of industrial effluents using in vitro bioassays combined with chemical analysis

Abstract: Wastewaters from various industries are a main source of the contaminants in aquatic environments. The authors evaluated the hormonal activities (estrogenic/anti‐estrogenic activities, androgenic/anti‐androgenic activities) and genotoxicity of various effluents from textile and dyeing plants, electronic and electroplate factories, pulp and paper mills, fine chemical factories, and municipal wastewater treatment plants in the Pearl River Delta region by using in vitro bioassays (yeast estrogen screen [YES]; yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Similarly, Fang et al (2012) evaluated the genotoxicity of wastewaters from various industries using the SOS/umu test combined with target chemical analyses; they concluded that the polycyclic aromatic hydrocarbons (PAHs) detected were only a minor contributor to the genotoxicity of the samples and that some nontarget compounds in the effluents were responsible. Actually, in previous studies, a variety of genotoxic compounds, not limited to the ones selected in this study, were detected in the water (Bu et al, 2013(Bu et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fang et al (2012) evaluated the genotoxicity of wastewaters from various industries using the SOS/umu test combined with target chemical analyses; they concluded that the polycyclic aromatic hydrocarbons (PAHs) detected were only a minor contributor to the genotoxicity of the samples and that some nontarget compounds in the effluents were responsible. Actually, in previous studies, a variety of genotoxic compounds, not limited to the ones selected in this study, were detected in the water (Bu et al, 2013(Bu et al, , 2015.…”
Section: Discussionmentioning
confidence: 99%
“…It is not uncommon that effluents after the wastewater treatment retain genotoxic activity (Lindström-Seppä et al, 1998;Žegura et al, 2009;Xavier et al, 2011;Fang et al, 2012;Vincent-Hubert et al, 2012). According to Lindström-Seppä et al (1998) the toxic activity of paper mill wastewaters is reduced by chemical treatment, but not by biological purification, while mutagenic activity is efficiently reduced during both chemical and Table 6 The mutagenic activity of raw and biologically treated Paper mill A effluents and recipient surface waters determined with the Ames MPF™ 98/100 Aqua assay on S. typhimurium without and with metabolic activation (S9).…”
Section: Cytotoxic and Mutagenic/genotoxic Activity Of Un-concentratementioning
confidence: 98%
“…For the description of sampling locations, see Table 1 the two paper mills reduced cell viability by N 25% or induced increase in β-galactosidase activity for N1.5-fold above the control, indicating that all samples were negative in this assay (Supplementary material Tables S1 and S2). Paper mill effluents and recipient surface waters have been reported to be genotoxic in the SOS/umuC assay (Rao et al, 1995;Fang et al, 2012); however, in these studies concentrated water samples, suspended particulate matter or extracts from sediments or organisms were tested. In the Ames MPF™ 98/100 Aqua assay Paper mill A effluents were not mutagenic ( Table 6).…”
Section: Cytotoxic and Mutagenic/genotoxic Activity Of Un-concentratementioning
confidence: 99%
“…Ihara et al, 2014;Rao et al, 2014) and this has been attributed to a range of factors from the presence of industrial compounds (e.g. Fang et al, 2012) to potential matrix effects from organic matter (e.g. Conroy et al, 2007).…”
Section: Introductionmentioning
confidence: 99%